DNA hypomethylation-mediated upregulation of GADD45B facilitates airway inflammation and epithelial cell senescence in COPD - Yuan Zhan; Qian Huang; Zhesong Deng; Shanshan Chen; Ruonan Yang; Jiaheng Zhang; Yating Zhang; Maocuo Peng; Jixing Wu; Yiya Gu; Zhilin Zeng; Jungang Xie (Journal of Advanced Research)
Introduction: Chronic obstructive pulmonary disease (COPD) is a heterogeneous disease typically characterized by chronic airway inflammation, with emerging evidence highlighting the driving role of cellular senescence-related lung aging. Accelerated lung aging and inflammation mutually reinforce each other, creating a detrimental cycle that contributes to disease progression. Growth arrest and DNA damage-inducible (GADD45) family has been reported to involve in multiple biological processes, including inflammation and senescence. However, the role of GADD45 family in COPD remains elusive. Objectives: To investigate the role and mechanism of GADD45 family in COPD pathogenesis. Methods: Expressions of GADD45 family were evaluated by bioinformatic analysis combined with detections in clinical specimens. The effects of GADD45B on inflammation and senescence were investigated via constructing cell model with siRNA transfection or overexpression lentivirus infection and animal model with Gadd45b knockout. Targeted bisulfite sequencing was performed to probe the influence of DNA methylation in GADD45B expression in COPD. Results: GADD45B expression was significantly increased in COPD patients and strongly associated with lung function, whereas other family members presented no changes. GADD45B upregulation was confirmed in mice exposed by cigarette smoke (CS) and HBE cells treated by CS extract as well. Moreover, experiments involving bidirectional modulation of GADD45B expression in HBE cells further substantiated its positive regulatory role in inflammatory response and cellular senescence. Mechanically, GADD45B-facilitated inflammation was directly mediated by p38 phosphorylation, while GADD45B interacted with FOS to promote cellular senescence in a p38 phosphorylation-independent manner. Furthermore, Gadd45b deficiency remarkably alleviated inflammation and senescence of lungs in CS-exposed mice, as well as improved emphysema and lung function. Eventually, in vivo and vitro experiments demonstrated that GADD45B overexpression was partially mediated by CS-induced DNA hypomethylation. Conclusion: Our findings have shed light on the impact of GADD45B in the pathogenesis of COPD, thereby offering a promising target for intervention in clinical settings.